Desain Media Carrdsight Berbasis Website dengan Pendekatan Social Emotional Learning Menggunakan Carrd.Co pada Materi Nilai Berkebhinekaan Global - Sri Murni; Shafa Nur Azizah; Eis Tria Kurnia; Diana Anggraini (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This research is motivated by the development of the industrial revolution 4.0 era and the need for teaching materials to improve student character based on the independent curriculum. Therefore, a design and trial of website-based Carrdsight teaching materials with a Social Emotional Learning (SEL) approach on Pancasila Student Profile material on Global Diversity Values was designed. This research is a Research and Development (R&D) study using the Borg & Gall procedure design. This research was conducted in SMP Yayasan Pendidikan Panjang Lampung. The subjects of this research were media design experts and seventh grade students of SMP Yayasan Pendidikan Panjang Lampung. The object of this research is Media Carrdsight teaching materials with SEL approach on Pancasila Student Profile material on Global Diversity Value. The data taken in this study are validity and response questionnaire data. The collected data were analysed using qualitative and quantitative descriptive analysis. The developed website media was declared very valid with a percentage of 83.52% by media experts and material experts, a practicality assessment of 80.45% by Guidance and Counselling teachers and received a very good response with a percentage of 85% from students. Based on the results of the study, it can be concluded that the website-based Carrdsight teaching materials Carrd.co with the SEL approach on the Pancasila Student Profile material on Global Diversity Values developed are valid and good.